Optimising Recovery of Vine Performance Following Irrigation During Extended Periods of Water Deficit - Zerihun, Ayalsew; Gibberd, Mark (Grape and Wine Research and Development Corporation, 2012)
The project reported here was undertaken in a commercial Shiraz vineyard in the Great Southern wine region of WA. Production in this region is predominantly rain-fed with less than 1 ML/ha supplementary irrigation input. In such systems with limited irrigation water availability, irrigation is necessarily applied at low volumes and infrequently – i.e., vines can become water stressed for extended periods of water deficits. The severity of stress may vary spatially within a vineyard block. These production systems, in particular vine functioning under such operational practices, have received little research attention. This project was thus aimed at examining vine physiological performance during extended periods of water deficits and recovery following small volume irrigation application (under commercial management practice). Variables examined included leaf level gas exchange, light energy utilisation/dissipation, leaf water status, sap flow and utilisation of applied irrigation water. Additionally, wine quality assessments were carried out in collaboration with a co-located and linked GWRDC Soil and Water Initiative project. The study vineyard block had considerable spatial variation in vine vigour. Variation in vigour had significant influence on nearly all attributes examined.For example, vines from the higher end of the vigour spectrum showed higher leaf photosynthesis and stomatal conductance rates, utilisation of absorbed light energy in photochemistry, sap flow rates and leaf water status than vines from the low vigour zones of the vineyard. At least in terms of leaf water status, low vigour vines showed rapid recovery following small volume irrigation although the recovery lasted for only a short period. A further consistent and notable finding was an apparently reduced capacity of vines from the low vigour zones of the vineyard to utilise applied water. Multivariate analyses of wine quality measures (sensory attributes and chemistry) showed significant differences between vintages, while there were also consistent “quality” differentiations between high and low vigour zones within vintages.